Urgensi Bimbingan Agama Terhadap Calon Pengantin Usia Muda Untuk Mewujudkan Keluarga Sakinah Mawaddah Dan Warahmah Di KUA Kecamatan Talawi Kabupaten Batubara - Siagian, Ronauli Dania; Misrah, Misrah (Jayapangus Press, 2024)
Marriage in Islam aims to build a sakinah, mawaddah warahmah family. A sakinah family, mawaddah warahmah is the dream of many husband and wife couples. The aim of this research is to determine the urgency of religious guidance for young prospective brides and grooms to create a sakinah, mawaddah and warahmah family. This guidance is carried out to provide understanding and knowledge for prospective couples so they can build a harmonious household. The method used in this research is a descriptive qualitative method and the data collection techniques used in this research are interviews, observation and documentation as data collection. The research results show that religious guidance is very relevant and important, especially in the context of a society where many people still marry at a young age. Young marriages are often faced with various challenges and risks, such as a lack of knowledge about marital responsibilities and difficulties in managing conflict. Therefore, premarital religious guidance can function as a means to provide a better understanding of religious values, and provide skills in managing married life. Religious guidance can help reduce the risk of divorce, improve marital well-being, and strengthen the foundations of a healthy and happy family.